Tax reform and the environment in developing economies: Is a double dividend possible? - Ian Coxhead (Fondazione Eni Enrico Mattei (FEEM), 2000)
We reconsider some analytical arguments on the double dividend, focusing on the small open developing economy case. Compared with the large, mature industrial economies usually considered, such economies differ in several respects, including the structure of tax revenues, commodity pricing and sectoral factor intensities. While a double dividend from environmentally-motivated taxes is not assured, the range of conditions for its existence seems broader than usually implied. Empirically, the scope for achieving both environmental improvements and diminished excess burden in developing economies may be greater as a side-effect of the reform of existing taxes than from imposition of explicit environmental taxes.
Keywords: Q28; O13; F18; 330; Double dividend; tariff; trade policy; developing economies; Thailand; Ökosteuer; Kleine offene Volkswirtschaft; Außenhandelspolitik; Handelsliberalisierung; Wohlfahrtsanalyse; Theorie; Entwicklungsländer; Thailand; Doppelte Dividende